2014
DOI: 10.1007/s00737-014-0445-4
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum bonding: the role of perinatal depression, anxiety and maternal–fetal bonding during pregnancy

Abstract: Adverse effects of perinatal depression on the mother-child interaction are well documented; however, the influence of maternal-fetal bonding during pregnancy on postpartum bonding has not been clearly identified. The subject of this study was to investigate prospectively the influence of maternal-fetal bonding and perinatal symptoms of anxiety and depression on postpartum mother-infant bonding. Data from 80 women were analyzed for associations of symptoms of depression and anxiety as well as maternal bonding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
218
5
12

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 318 publications
(269 citation statements)
references
References 52 publications
20
218
5
12
Order By: Relevance
“…According to Spratt et al [1] during the early phase of childhood, brain development was shown to be susceptible to environmental influences and nurturing care. Another study conducted by Dubber, Reck, Muller, and Gawlik [30], showed a link between emotional disorders in childhood and impaired maternal bonding. The research provides the APN with a background of potential causes of brain and emotional development about impaired maternal-newborn bonding.…”
Section: Impact On Advanced Nursing Practicementioning
confidence: 93%
See 1 more Smart Citation
“…According to Spratt et al [1] during the early phase of childhood, brain development was shown to be susceptible to environmental influences and nurturing care. Another study conducted by Dubber, Reck, Muller, and Gawlik [30], showed a link between emotional disorders in childhood and impaired maternal bonding. The research provides the APN with a background of potential causes of brain and emotional development about impaired maternal-newborn bonding.…”
Section: Impact On Advanced Nursing Practicementioning
confidence: 93%
“…Current research lacked in providing a clear understanding of the potential risk for abuse or neglect. Dubber et al [30] concluded that a negative maternalnewborn bond had a significant impact on maternal depression and emotional health. Maternal depression or alteration in emotional health correlates in some cases with child abuse or neglect.…”
Section: Impact On Nursing Researchmentioning
confidence: 99%
“…Así mismo, la investigación de Lickenbrock y Braungart-Rieker (5) , sobre el apego sano, concluye que no solamente la sensibilidad de las madres se relaciona con el apego, sino también otros factores como el nivel socioeconómico, que afecta a la calidad de la crianza y el comportamiento social de los niños. Dubber et al (6) , indican que el efecto de la sensibilidad de las madres, también dependió de los niveles de recursos económicos de la familia y que frente a condiciones más difíciles como: los padres más jóvenes, menos educados y con ocupaciones menos remunerados, existe mayor tendencia al apego en riesgo. Los factores como la falta de…”
Section: Discussionunclassified
“…El estudio de Koroleff y Nóblega 7 mostró que las madres sin ninguna instrucción o educación relacionada con la interacción con su recién nacido, tenían bajas puntuaciones para un adecuado apego, donde el 46,2% de ellas tenía secundaria completa. Así mismo lo afirmó el estudio de Escobar 5 y el estudio de Dubber et al (6) , quienes refieren que las madres menos educadas tienen una mayor tendencia al apego en riesgo, pero no hubo significancia estadística.…”
Section: Discussionunclassified
See 1 more Smart Citation